Evolution of Crystallinity and Texturing on 120 MeV Au Ion Irradiation on NiO Thin Films - Mallick P.; Rath C.; Agarwal D.C.; Biswal R.; Behera D.; Avasthi D.K.; Kanjilal D.; Satyam P.V.; Mishra N.C. (My University, 2025)
NiO thin films grown on Si(100) substrate by electron beam evaporation and sintered at 500 °C and 700 °C were irradiated with 120 MeV 197Au9+ ions. The FCC structure of the sintered films was retained up to the highest fluence (3 × l013 ions.cm-2) of irradiation. As against the expected amorphization due to ion irradiation when electronic energy loss exceeds certain threshold value, we observe an improvement of crystallinity and grain orientation at certain fluences of irradiation. © 2008 American Institute of Physics.